KONEKSITAS TARI DAN MUSIK PADA TARI KELANA GAYA SURAKARTA - Maryono Maryono (Greget, 2021)
Klana Dance Surakarta style there are at least three main versions that can be traced, namely Kelana dance version S. Ngaliman, version of S.Maridi, and Version Sunarno Purwo Lelono. The three versions of Kelana dance in the groove do not have a prominent difference, but there are quite strong differences and very principles, especially in pacak and wiled sustainability that I observed from 1979 to the 2010s. The connection of dance and music in Surakarta Style Kelana dance shows the existence of a blend and harmony formed from the role of music to dance that serves as a pointer of content, illustration/nglambari, membungkus/mungkus, and nyawiji so as to form a Kelana dance Surakarta Style that is dashing, sigrak, spirit, firm and authoritative. The basic principle that each element in Kelana dance is a visual form that is artistic has shown coherence between elements and total connection so that it can function as a means of expression of the artist steadily.Keywords: music and Kelana dance